The Usage Of Visual Metaphors In Tourism Advertisement As A Potential Persuasive Method In Sara Wak Tourism Advertisement - Haji Siri , H.; Halim, H. (Universiti Malaysia Sarawak (UNIMAS), 2011)
This is a study on the effects of visual metaphors in tourism advertisement. In advertising the uses of visual metaphors are commonly applied to express meaning more creatively while in the same time without losing the whole context of the actual message conveyed. The use of photography in tourism marketing is becoming more common now that technology of photography become more evolve compare to the year before. Appropriate use of strong visual images in tourism marketing will increase the chance of influencing prospective tourists on choosing the tourism site. One of them is metaphor. Metaphors are used in advertisement as a way of setting themselves apart from the other advertisements while giving them positive impression which will eventually persuade the prospective tourists to visit the place advertised. Besides that it motivates them to experience the same experience as depicted in visual images within the advertisement. This study also studies the persuasive effect of visual metaphors in advertising. The images constructed will be based on three experimental conditions : non-metaphorical advertisement, metaphorical advertisement with verbal anchoring, and metaphorical advertisement without verbal anchoring. The difference between the first and second condition is rhetorical style while the difference between the second and the third condition is argument modality. The use of qualitative and quantitative approach will be implemented in this research whereby feedback from respondents will be the main primary data.